Pendampingan Dan Pembinaan Pembelajaran Dengan Strategi “LESSUGAR” (Lingkungan Sebagai Sumber Belajar) Di TK Restu Ibu Kota Depok - Ditta Kristina Putri (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Mentoring and coaching of learning at Restu Ibu Kindergarten is carried out by implementing the “Lessugar” strategy, which utilizes the environment as a source of learning. This strategy aims to realize the concept of Independent play and Independent learning, where children are free to explore and learn according to their interests and potential. Through direct interaction with the surrounding environment, children can develop curiosity, critical reasoning skills, and social skills. This contextual learning provides a more meaningful learning experience, so that children are able to connect the knowledge gained with their daily lives. The results of the mentoring show that this strategy is able to create a pleasant learning atmosphere and support the holistic development of early childhood. The lessugar strategy is expected to continue to be developed as an innovative learning model that supports inclusive and participatory early childhood education.